A 300 GHz CMOS Transmitter Front-End for Ultrahigh-Speed Wireless Communications - Tuan Anh Vu; Minoru Fujishima (Institute of Advanced Engineering and Science, 2017)
This paper presents a 300 GHz transmitter front-end suitable for ultrahigh-speed wireless communications. The transmitter front-end realized in TSMC 40 nm CMOS consists of a common-source (CS) based doubler driven by a two-way D-band power amplifier (PA). Simulation results show that the two-way D-band PA obtains a peak gain of 21.6 dB over a -3 dB bandwidth from 132 GHz to 159 GHz. It exhibits a saturated power of 7.2 dBm and a power added efficiency (PAE) of 2.3%, all at 150 GHz. The CS based doubler results in an output power of 0.5 mW at 300 GHz. The transmitter front-end consumes a DC power of 205.8 mW from a 0.9 V supply voltage while it occupies an area of 2.1 mm2.